2021
DOI: 10.1021/acsami.1c03158
|View full text |Cite
|
Sign up to set email alerts
|

Endorsing Organic Porous Polymers in Regioselective and Unusual Oxidative C═C Bond Cleavage of Styrenes into Aldehydes and Anaerobic Benzyl Alcohol Oxidation via Hydride Elimination

Abstract: Oxidative cleavage of styrene CC double bond is accomplished by employing a nitrogen-rich triazine-based microporous organic polymer as an organocatalyst. We report this regioselective reaction as first of its kind with no metal add-ons to afford benzaldehydes up to 92% selectivity via an unusual Wackertype CC bond cleavage. Such a reaction pathway is generally observed in the presence of a metal catalyst. This polymer further shows high catalytic efficiency in an anaerobic oxidation reaction of benzyl alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…2b). Importantly, unlike most previous studies, 24,27,56,57 there was no need for any additives that would present extra challenges for product purification. However, in the absence of the V-Cd-MOF , only less than 10% of BA was converted under otherwise identical conditions (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…2b). Importantly, unlike most previous studies, 24,27,56,57 there was no need for any additives that would present extra challenges for product purification. However, in the absence of the V-Cd-MOF , only less than 10% of BA was converted under otherwise identical conditions (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Efforts have been made in realizing at least some of the abovementioned goals. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] For example, Stahl and co-workers reported the selective oxidation of alcohols to aldehydes with O 2 catalyzed by Fe(NO 3 ) 3 /TEMPO (TEMPO: 2,2,6,6-tetramethylpiperidine-N-oxy); 26 a team led by Beller achieved the oxidation of benzyl alcohol to benzaldehyde with nearly 100% selectivity using H 2 O 2 as an oxidant and nanostructured Fe 2 O 3 as a catalyst; 15 Li and co-workers developed a CoAlbased composite catalyst capable of catalyzing additive-free selective oxidation of alcohols with O 2 ; 21 and Tsukuda et al succeeded in oxidizing with O 2 benzyl alcohol derivatives using an Au 24 cluster-based catalyst and K 2 CO 3 as an additive. 24 Notwithstanding the progress made, a catalyst possessing all the desirable traits has yet to appear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is affirmative to mention that increasing the overall electronic conjugation lowers the band gap more than that of the monomeric unit. 31 This provides better electron accessibility from MOP-TA for interacting with the α-carbon of the benzyl alcohols that make the Cα-H bond labile (Fig. S7 †).…”
Section: Role Of Catalystmentioning
confidence: 99%
“…Further investigations suggested that heteroatom inclusion in the backbone of the polymer led to structural defects that enhance the catalytic activity by modulating multiple active sites. [31][32][33] This inspires us to think of metal-free POPs as a sustainable and benign organocatalyst for the synthesis of valued quinoline scaffold from alcohols via in situ generation of H 2 with proper reaction conditions.…”
Section: Introductionmentioning
confidence: 99%